2015
DOI: 10.1017/jfm.2015.341
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved flow dynamics and Reynolds number effects at a wall–cylinder junction

Abstract: This study investigated the physics of separated turbulent flows near the vertical intersection of a flat wall with a cylindrical obstacle. The geometry imposes an adverse pressure gradient on the incoming boundary layer. As a result, flow separates from the wall and reorganizes to a system of characteristic flow patterns known as the horseshoe vortex. We studied the time-averaged and instantaneous behaviour of the turbulent horseshoe vortex using planar time-resolved particle image velocimetry (TRPIV). In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 35 publications
12
41
0
Order By: Relevance
“…This finding differs markedly from observations for rectangular/circular piers for which the maximum scour depth d s is seen to occur at the upstream face of the pier (e.g., Melville 1975;Breusers et al 1977;Lagasse et al 2010). The different locations of maximum scour depth for rectangular/circular piers and sharp-nose piers may be due to the following two factors related to the flow around the pier: First, the turbulent horseshoe vortex (THV) system, which is known to be the primary factor causing scour at the upstream face of rectangular/circular piers (Kirkil et al 2008;Escauriaza and Sotiropoulos 2011;Link et al 2012;Apsilidis et al 2015;Bouratsis et al 2017;Chen et al 2017), has been observed by previous researchers (Shen et al 1966;Breusers et al 1977) to be not as well pronounced at the leading edge of sharp-nose piers. Second, the flow separation and the shedding of the two shear-layers at the two side corners of a sharp-nose pier increases bed shear stresses at these corners (Khosronejad et al 2012;Vijayasree et al 2017) and may thereby lead to maximum scour occurring at these locations.…”
Section: Scour Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding differs markedly from observations for rectangular/circular piers for which the maximum scour depth d s is seen to occur at the upstream face of the pier (e.g., Melville 1975;Breusers et al 1977;Lagasse et al 2010). The different locations of maximum scour depth for rectangular/circular piers and sharp-nose piers may be due to the following two factors related to the flow around the pier: First, the turbulent horseshoe vortex (THV) system, which is known to be the primary factor causing scour at the upstream face of rectangular/circular piers (Kirkil et al 2008;Escauriaza and Sotiropoulos 2011;Link et al 2012;Apsilidis et al 2015;Bouratsis et al 2017;Chen et al 2017), has been observed by previous researchers (Shen et al 1966;Breusers et al 1977) to be not as well pronounced at the leading edge of sharp-nose piers. Second, the flow separation and the shedding of the two shear-layers at the two side corners of a sharp-nose pier increases bed shear stresses at these corners (Khosronejad et al 2012;Vijayasree et al 2017) and may thereby lead to maximum scour occurring at these locations.…”
Section: Scour Mapmentioning
confidence: 99%
“…Experimental and computational research, particularly over the last few decades, have enhanced significantly the understanding of the scour process around bridge piers by describing the underpinning science, particularly of the flow field and the turbulent horseshow vortex (THV) system upstream of circular and rectangular piers (e.g., Melville and Coleman 2000;Kirkil et al 2008;Escauriaza and Sotiropoulos 2011;Link et al 2012;Apsilidis et al 2015;Unsworth 2016;Bouratsis et al 2017;Chen et al 2017;Ettema et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and computational research have significantly enhanced the understanding of the local scour process around bridge piers by describing the underpinning science, particularly of the vortex systems and scour patterns around circular and rectangular pier shapes [2,[14][15][16][17][18][19][20]. Recently, Manes and Brocchini [21] derived a new predictive formula to calculate the scour depth at piers, which merges the phenomenological theory of turbulence with empirical observations.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to better understand the physics behind scour, fluid flows around wall-mounted obstacles, such as cylinders or wings, have been described from experimental observations [3][4][5][6] or numerical simulations [7][8][9]. These studies examined the time-averaged and time-resolved characteristics of flows around the obstacles.…”
Section: Introductionmentioning
confidence: 99%